Effect of humic substances on phosphorus removal by struvite precipitation. (December 2015) - Zhou, Zhen; Hu, Dalong; Ren, Weichao; Zhao, Yuzeng; Jiang, Lu-Man; Wang, Luochun
Highlights: Inhibitory effect of humic substances on struvite precipitation was studied. Humic substances inhibited struvite precipitation at pH 8.0–9.0 and low Mg/P ratio. Humic substances changed structure and morphology of precipitated struvite crystals. Coprecipitation of humic substances compromised precipitated struvite purity. Abstract: Humic substances (HS) are a major fraction of dissolved organic matters in wastewater. The effect of HS on phosphorus removal by struvite precipitation was investigated using synthetic wastewater under different initial pH values, Mg/P molar ratios and HS concentrations. The composition, morphology and thermal properties of harvested precipitates were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM) and thermo-gravimetric analysis (TGA), respectively. It showed that inhibition effect of HS reached its maximum value of 48.9% at pH 8.0, and decreased to below 10% at pH > 9.0. The increase of Mg/P ratio enhanced phosphorus removal efficiency, and thus reduced the influence of HS on struvite precipitation. At pH 9.0, the inhibitory effect of initial HS concentration matched the modified Monod model with half maximum inhibition concentration of 356 mg L −1, and 29% HS was removed in conjunction with struvite crystallisation. XRD analysis revealed that the crystal form of struvite precipitates was changed in the presence of HS. The morphology of harvested struvite was transformed from prismatic to pyramid owing to the coprecipitation of HS on crystal surface. TGA results revealed that the presence of HS could compromise struvite purity.